Multinational firms in tax havens: Corporate motives, regulatory countermeasures, and recent statistics - Marcel Olbert; Christoph Spengel; Stefan Weck (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
We investigate multinational firms' activities in tax havens and regulatory efforts to curb these activities in three steps. First, we discuss the evolution of information exchange and disclosure regimes among tax authorities, with a focus on the recent Countryby-Country (CbC) reporting regimes, designed to uncover and address tax haven usage by multinational firms. Second, we review existing empirical literature on multinational firms' tax haven utilization, specifically examining the impact of information exchange regulations and Country-by-Country Reporting. Third, we augment the current empirical evidence by presenting tax haven entity statistics from 2007 to 2021 for a representative multinational firm sample, sourced from Bureau van Dijk (BvD) Orbis and the aggregated CbC data provided by the Organisation for Economic Co-operation and Development (OECD). Our analysis suggests that, if exploited systematically, the recent Orbis database provides granular coverage of multinational firms' subsidiaries worldwide, including tax haven entities in jurisdictions without disclosure mandates and information sharing agreements. Our findings reveal that multinational firms' ownership of tax haven entities peaked in 2015, with over 50,000 legal entities incorporated in tax havens (30,000 in Big8 tax haven jurisdictions). Although the growth of tax haven entities slowed after 2015, the overall number remains substantial as of 2021. Furthermore, European multinationals experienced a modest decline in tax haven entities following the implementation of mandatory private CbCR. We conclude by discussing policy implications and suggesting avenues for future research.
Keywords: H20; H25; H26; F23; P45; 330; Tax havens; multinational firms; tax avoidance; Country-by-Country Reporting; transparency; information exchange